Take the 2-minute tour ×
MathOverflow is a question and answer site for professional mathematicians. It's 100% free, no registration required.

Is it true that groups $\langle a,b \mid a^n b^k=b^ka^{n+1}, b^la^s=a^sb^{l+1}\rangle$ are non-trivial for almost all (in any sense:))) $n,k,l,s\in\mathbb N$?

share|improve this question
3  
I took the liberty to edit the LaTeX: < and > to \langle and \rangle and | to \mid. I believe this improves readability. –  José Figueroa-O'Farrill Sep 27 '11 at 8:41

1 Answer 1

up vote 16 down vote accepted

The group is always trivial. Indeed, $a^{-ns}b^{l^n}a^{ns}=b^{(l+1)^n}$. On the other hand, $a^{ns}=b^ka^{(n+1)s}b^{-k}$. Substitute $a^{ns}$ from the second equality to the first. You will get that $a^{(n+1)s}$ conjugates $b^{l^n}$ to $b^{(l+1)^n}$. Since $a^{ns}$ does the same, you get that $a^s$ commutes with $b^{l^n}$. Hence $b^{l^n}=b^{(l+1)^n}$ and $b$ is torsion, $b^p=1$. Similarly, $a$ is torsion, $a^q=1$. Notice also that $p=(l+1)^n-l^n$ is coprime with $l$ and $q$ is coprime with $n$. Now we have $b^{-kp}a^{n^p}b^{kp}=a^{(n+1)^p}$. Hence $a^{n^p}=a^{(n+1)^p}$. We already know that $a^{n^l}=a^{(n+1)^l}$. Suppose that the order of $a$ is $t$. Then $t$ divides both $(n+1)^l-n^l$ and $(n+1)^p-n^p$ and is co-prime with $n$. Then $t$ divides $$(n+1)^p-n^p-(n+1)^p+n^l*(n+1)^{p-l}=-n^p+n^l*(n+1)^{p-l}.$$ Since $t$ and $n$ are co-prime, $t$ divides $(n+1)^{p-l}-n^{p-l}$. Proceed by using the Euclidean algorithm. Since $p$ and $l$ are co-prime, we get that $t$ divides $(n+1)-n=1$, so $a=1$. Similarly $b=1$ and the group is trivial.

share|improve this answer
    
I'm not following this. Why does $a^s$ commute with $b^{l^n}$? –  Neil Strickland Sep 27 '11 at 13:45
    
Elementary, Neil: Substitute $a^{ns}$ from the second equality to the first, then cancel extra $b$'s. –  Mark Sapir Sep 27 '11 at 14:35
    
I added an explanation. –  Mark Sapir Sep 27 '11 at 14:38
    
how did you obtain the first identity equation? –  Nikita Kalinin Sep 27 '11 at 19:34
    
@Nikita: Suppose for simplicity that $a^2b^3a^{-2}=b^7$ (the same works for every other choice of exponents). Then $$a^2b^9a^{-2}=(a^2b^3a^{-2})^3=b^{21}.$$ Now $$a^4b^9a^{-4}=a^2b^{21}a^{-2}=(a^2b^3a^{-2})^7=a^{49}.$$ Notice that $9=3^2, 49=7^2$. I guess you can do it in general now. –  Mark Sapir Sep 27 '11 at 20:30

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.